The Idea of Congruence between Image and Society Stereotype on Attitude toward Tourist Destination - RAHAYU, Sri; ASSAURI, Sofjan; HERUWASTO, Ignatius (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).06, 2017)
This article aims to provide a conceptual framework that depicts the matching between destination image, destination society stereotype in the context of consumer’s behavior, and tourist destination. Using literature review and empirical researches, the present study attempts to formulate propositions that connect destination image and destination society stereotype in creating and/or improving positive attitude toward tourist destination. Based on literature review and empirical researches, the concept fit as matching can be implemented to achieve congruence between destination image and destination society stereotype in order to develop more optimal (positive) attitudes toward tourist destination. The present study also offers the concept of relationship closeness and image formation type as moderation to strengthen the development of positive attitudes. At the end of this paper, several suggestions and recommendations are provided to follow up the proposed notions in the form of empirical research. They include the dimensions and elements of each concept that need further exploration. This paper provides conceptual framework for practitioners and academics who are looking for theoretical support pertaining to destination image and destination society stereotype in the context of tourist destination. In addition, this paper also offers the concept of fit as matching to build congruence between destination image and destination society, as an instance of the application of strategic discipline in the context of marketing and tourism.  The propositions in this paper contain the concepts of relationship closeness and image formation type as variables of moderation which may provide further contribution to the literature of tourism marketing.